(untitled) - Buková, Bibiána; Valovič, Radoslav (Doprava a spoje, 2005)
Logistics is defined as a business planning framework for the management of material, service, information and capital flows. It includes the increasingly complex information, communication and control systems required in today's business environment. Logistics offers opportunities of implementation of information and communication technologies (ICT). This is e-logistics and together with ICT brings for transport operators and customers many advantages, e.g. lower costs, more automation, systematic reactions and answers to customer's requests.